Tibet through a Native Lens: Charles Alfred Bell’s Image-Archive and the Roles of his Photographic Interlocutors (HIMALAYA, 2025)
This essay attempts to foreground the question of native agency in the making of the photographic archive of Charles Alfred Bell, British Political Officer for Sikkim, Bhutan and Tibet. It seeks to approach a new hermeneutics of British imperial archive-making vis-á-vis Tibet by assessing not only how native agency variously informed the sacerdotal, epistemic and technical content of most of Bell’s photographic archive, but also how such agency was central to its very process of visual production. By examining the roles of Rabden Lepcha, Sonam Wangyal or Palhese and Kartick Chandra Pyne, apropos their contribution to Bell’s visual archive, the essay shows how British imperial knowledge-construction on Tibet deployed native agency, thereafter relegating them (mostly) to archival silence. In the process, the essay demonstrates how these silences were not merely accidental, but fundamental to the process of knowledge-production on Tibet.